PENGGUNAAN GRAMATIKA DALAM WACANA POLITIK: STUDI REPRESENTASI BAHASA SEBAGAI SISTEM MAKNA SOSIAL DAN POLITIK - Santoso, Anang (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2008)
The grammar of the Indonesian language is greatly made use of inpolitical discourse and especially after the era of the Old Order. Via grammaticalforms, the political elite fights for its power and ideology, both explicitly andimplicitly, causing an unbalanced political communication. A research study thisarticle is about was conducted to (1) describe and interpret the utilization ofgrammaticality in political discourse and (2) clarify why certain grammaticalforms are paid special attention while others are not.The study applied a critical qualitative approach with a